Identification of indicators to measure polarization among scientific staff in Bolivian public universities - Caballero Calle, Edwin Ebert (2024)
The study proposes indicators to evaluate the level of polarization among scientific staff at public universities in Bolivia, identifying polarization as a significant barrier to collaboration and knowledge generation. Grounded in theories of knowledge management and organizational development, it emphasizes the importance of a conducive environment for innovation and cooperation. The research formulates specific indicators across various dimensions such as political ideology, interpersonal conflicts, and team collaboration. The methodology includes creating a survey to gather data and measure these factors. The study concludes that polarization negatively impacts collaboration and innovation, proposing strategies to mitigate these effects and foster a more collaborative and productive work environment.